Efektivitas dan Efisiensi Dana Desa (DD) Terhadap Pemberdayaan Masyarakat dan Pembangunan Desa Di Desa Lebeng Barat Kabupaten Sumenep - Raudhatul Ingkiat; Diana Dwi Astuti; Hamzah Fansuri (Institut Teknologi dan Sains Mandala, 2022)
This study aims to analyze the level of effectiveness and efficiency of Village Fund management on Community Empowerment and Village Development in Lebeng Barat Village, Sumenep Regency. This study contains the effectiveness and efficiency of the use of village funds for community empowerment and development in Lebeng Barat Village, Sumenep Regency. This study uses a quantitative descriptive method with data on income realization, expenditure realization and expenditure targets by using the ratio of effectiveness and efficiency. The results of this study indicate that the level of effectiveness of village funds in Lebeng Barat Village in 2019 is in the effective category because the effectiveness of village funds reaches 99%, namely by prioritizing infrastructure development and community empowerment, while the efficiency level of Village Funds in Lebeng Barat Village is 95%, where this result shows the inefficiency of village funds in Lebeng Barat Village, Sumenep District. This is due to the occurrence of waste and there is a financial allocation calculation that is not done carefully in financing the activities carried out by the village.